2021
DOI: 10.1371/journal.pntd.0009515
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approach to the epidemiology of urinary schistosomiasis in France

Abstract: Background The diagnosis of urogenital schistosomiasis is based on the complementarity of serological technique and microscopic examination (ME). Between 2015 and 2019, the number of urinary schistosomiasis tests received in our laboratory increased sharply from 300 to 900 per year. Therefore, we wanted to evaluate the reliability of urine microscopic examination (ME, reference and routine technique) from urine sample by comparing it to other techniques (antigenic technique and PCR). To this end, we optimized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(78 reference statements)
0
2
0
3
Order By: Relevance
“…They have found also less day-today variation of eggs count in urine testing over three days. In another study, the authors have given more details on the correlation between the eggs count and the Ct value [30]. They have found that a single schistosome egg correspond to the Ct-value at 20+/-2.…”
Section: Discussionmentioning
confidence: 98%
“…They have found also less day-today variation of eggs count in urine testing over three days. In another study, the authors have given more details on the correlation between the eggs count and the Ct value [30]. They have found that a single schistosome egg correspond to the Ct-value at 20+/-2.…”
Section: Discussionmentioning
confidence: 98%
“…They also found less day-to-day variation of egg count in urine testing over 3 days. In another study, the authors gave more details on the correlation between egg count and Ct value [ 30 ]. They found that a single schistosome egg corresponded to the Ct value at 20 ± 2.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты проведенного анализа свидетельствуют о широкой географии проведенных исследований: большая их часть выполнена в эндемичных регионах Юго-Восточной Азии, но также изучение проводилось в странах Европы, США, Африки [12][13][14][15]. Для подтверждения диагноза большинства трематодных инвазий используется микроскопия образцов стула пациента, так как метод является простым и доступным в выполнении, однако, позволяет выявить только инвазию средней и высокой интенсивности [12,16].…”
Section: современные технологии микроскопииunclassified
“…Для подтверждения диагноза большинства трематодных инвазий используется микроскопия образцов стула пациента, так как метод является простым и доступным в выполнении, однако, позволяет выявить только инвазию средней и высокой интенсивности [12,16]. Большей чувствительностью и универсальностью при низкой интенсивности инвазии обладает метод седиментации [15,17,18]. Микроскопия образцов фекалий, мочи или дуоденального содержимого требует обеспечение лаборатории световым микроскопом и квалицированным опытным персоналом, что не всегда возможно в эндемичных очагах трематодозов.…”
Section: современные технологии микроскопииunclassified
See 1 more Smart Citation